Concurrent Optical Gain Optimization and Electrical Tuning in Novel Oligomer:Polymer Blends with Yellow‐Green Laser Emission. Issue 1 (8th November 2018) - Zhang, Qi; Wei, Qi; Guo, Xiangru; Hai, Gang; Sun, Huizhi; Li, Jiewei; Xia, Ruidong; Qian, Yan; Casado, Santiago; Castro‐Smirnov, José Raúl; Cabanillas‐Gonzalez, Juan
Abstract: Electrically pumped organic lasing requires the integration of electrodes contact into the laser cavity in an organic light‐emitting diode (OLED) or organic field effect transistor configuration to enable charge injection. Efficient and balanced carrier injection requires in turn alignment of the energy levels of the organic active layers with the Fermi levels of the cathode and anode. This can be achieved through chemical substitution with specific aromatic functional groups, although paying the price for a substantial (and often detrimental) change in the emission and light amplifying properties of the organic gain medium. Here, using host–guest energy transfer mixtures with hosts bearing a systematic and gradual shift in molecular orbitals is proposed, which reduces the amplified spontaneous emission (ASE) threshold of the organic gain medium significantly while leaving the peak emission unaffected. By virtue of the low guest doping required for complete host‐to‐guest energy transfer, the injection levels in the blends are attributed to the host whereas the gain properties solely depend on the guest. It is demonstrated that the ASE peak and thresholds of blends with different hosts do not differ while the current efficiency of OLEDs devices is deeply influenced by molecular orbital tuning of the hosts. Abstract : Energy level engineering is requested in future electrically pumped organic lasers. Chemical modification of active layer using functional substitution group such as fluorine atom may introduce unpredictable damage on emission or gain of the medium. Constructing efficient energy transfer system allows isolate tuning of electrical property of the hosts while the gain property of the guest remains undisturbed.